Presentation: Healthy, Sick and Saved? - Cueto, Marcos (2000)
It is a special occasion to present this monographic issue of Allpanchis magazine dedicated to the topic of health and mountains in Peru. The motivation for programming this number is the verification that in recent years studies on perceptions, conditions, services and health policies in Peru have increased and deepened. These works allow us to understand the past and the current health situation in the country, as well as the challenges and changes that are necessary in this sector. In this way, they offer a long-term perspective on the structural conditions that affect the life, birth, well-being and death of the Peruvian population.